2017
DOI: 10.5863/1551-6776-22.6.406
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin Dosing and Monitoring in the Treatment of Cystic Fibrosis: Results of a National Practice Survey

Abstract: OBJECTIVES Vancomycin is commonly used in patients with cystic fibrosis (CF) to treat acute pulmonary exacerbations, but few guidelines exist to help dose and monitor patients. The objective of this study was to assess vancomycin use and monitoring strategies at Cystic Fibrosis Foundation (CFF)-accredited centers in hopes of developing and implementing vancomycin dosing and monitoring standards. METHODS An anonymous national cross-sectional survey of pharmacists affiliated with CFF-accredited pediatric and/or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
6
0
2
Order By: Relevance
“…Because of their frequent need for IV antibiotics, the potential use of concomitant nephrotoxic medications, and longer duration of antibiotic therapy, patients with CF are at higher risk of nephrotoxicity related to vancomycin 10 . In a 2017 national survey of Cystic Fibrosis Foundation Centers, 93% of pharmacists reported using serum trough to monitor vancomycin 11 . For this reason, little data is available in this patient population for monitoring vancomycin using two concentrations to estimate AUC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of their frequent need for IV antibiotics, the potential use of concomitant nephrotoxic medications, and longer duration of antibiotic therapy, patients with CF are at higher risk of nephrotoxicity related to vancomycin 10 . In a 2017 national survey of Cystic Fibrosis Foundation Centers, 93% of pharmacists reported using serum trough to monitor vancomycin 11 . For this reason, little data is available in this patient population for monitoring vancomycin using two concentrations to estimate AUC.…”
Section: Introductionmentioning
confidence: 99%
“…10 In a 2017 national survey of Cystic Fibrosis Foundation Centers, 93% of pharmacists reported using serum trough to monitor vancomycin. 11 For this reason, little data is available in this patient population for monitoring vancomycin using two concentrations to estimate AUC. Until October 2018, UKHC utilized trough monitoring for vancomycin therapies.…”
mentioning
confidence: 99%
“…After 3-5 doses or at least 24 hours of continuous infusion (in order to reach steady state), the serum vancomycin level is routinely determined (therapeutic drug monitoring, TDM). The target levels are a trough concentration of 10-15 mg/L or 15-20 mg/L [3,5] . Some studies reported that the trough concentration of vancomycin should be maintained at 20 mg/L or higher to reach a target value of the AUC/MIC ratio of 400 or higher [4] .…”
Section: Discussionmentioning
confidence: 99%
“…los aminoglucósidos pueden producir ototoxicidad, por lo que se debe realizar una evaluación auditiva (ver manifestaciones otorrinolaringológicas). 109 Fármaco que depende tanto del tiempo como de la concentración para ejercer su efecto bactericida. Se recomienda medir niveles peak y valle con el fin de aproximarse a un valor de área bajo la curva sobre la CIM, el cual, debe ser mayor a 400 µg/ml.…”
Section: Medición De Niveles De Aminoglucósidosunclassified